Memory reconsolidation and extinction in the crab: Mutual exclusion or coexistence? - Pérez-Cuesta, L.M. (2009)
A conditioned stimulus (CS) exposure has the ability to induce two qualitatively different mnesic processes: memory reconsolidation and memory extinction. Previous work from our laboratory has shown that upon a single CS presentation the triggering of one or the other process depends on CS duration (short CS exposure triggers reconsolidation, whereas a long CS exposure triggers extinction), both being mutually exclusive processes. Here we show that either process is triggered only after CS offset, ruling out an interaction as the mechanism of this mutual exclusion. Also, we show here for the first time that reconsolidation and extinction can occur simultaneously without interfering with each other if they are serially triggered by respective short and long CS exposures. Thus, we conclude that (1) one single CS presentation triggers one single process, after CS offset, and (2) whether memory reconsolidation and extinction mutually exclude each other or whether they coexist depends only on whether they are triggered by single or multiple CS presentations. © 2009 Cold Spring Harbor Laboratory Press.